Impaired Liver Size and Compromised Neurobehavioral Activity are Elicited by Chitosan Nanoparticles in the Zebrafish Embryo Model - Haissam Abou-Saleh (497840) (2019)
The use of chitosan nanoparticles (ChNPs) in various biological and environmental applications is attracting great interest. However, potential side effects related to ChNP toxicity remain the major limitation hampering their wide application. For the first time, we investigate the potential organ-specific (cardiac, hepatic, and neuromuscular) toxicity of ChNPs (size 100–150 nm) using the zebrafish embryo model. Our data highlight the absence of both acute and teratogenic toxic effects of ChNPs (~100% survival rate) even at the higher concentration employed (200 mg/L). Although no single sign of cardiotoxicity was observed upon exposure to 200 mg/L of ChNPs, as judged by heartbeat rate, the corrected QT interval (QTc, which measures the time between the start of the Q wave and the end of the T wave in the heart's electrical cycle), maximum cardiac arrest, and ejection fraction assays, the same dosage elicited the impairment of both liver size (decreased liver size, but without steatosis and lipid yolk retention) and neurobehavioral activity (increased movement under different light conditions). Although the observed toxic effect failed to affect embryo survival, whether a prolonged ChNP treatment may induce other potentially harmful effects remains to be elucidated. By reporting new insights on their organ-specific toxicity, our results add novel and useful information into the available data concerning the in vivo effect of ChNPs. Other Information Published in: Nanomaterials License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/nano9010122